Reading smallness: micro-spatial constructions in South Africa's literature of the interregnum - Henning, John (Department of English Language and Literature, 2024)
Twentieth-century South African literature is a subject often oversimplified by familiar binaries. These include the categories of apartheid and post-apartheid, metaphors of death and birth, and pre-occupations with the tensions between public and private life, township and suburb, and oppressor and oppressed. Such patterns of signification continue to chase their target – a centuriesold national symptomology – with dwindling degrees of success. This dissertation, in response, seeks out literary micro-spaces from the country's transition (or ‘interregnum') and reads them in terms of their incursive potential on the grand historical and spatial discourses in which they lie. To this end, the project takes its reader on a tour of small places. On one side is a compost hole from Ivan Vladislavić's Missing Persons (1989) – an evocator of the neuroses at the ‘heart of apartheid' – and, on the other, a one-room shack from Zakes Mda's Ways of Dying (1995) – an ostensible symbol of an early post-apartheid imaginary. The discussion stretching between these two points, as it moves from nests and tortoiseshells to graves and train carriages, advocates reduced frames of reading. In so doing, it draws attention at once to the claustrophobia of apartheid pettiness and, in the literary sensitivities that it precipitates, to growing associations between smallness and protest, smallness and vocality, smallness and poetry. I argue that micro-spaces are not only abundant in the literature of South Africa's political transition but also yield unique insights into the stubborn extension of its interregnum.